The uncanny inhumans (2015), volume 1 ebook Time crush. - Soule, Charles (The Uncanny Inhumans (2015), 2016)
Collects Uncanny Inhumans #0-4 and material from Free Comic Book Day 2015 Avengers. They fell to Earth; they changed the world — now Black Bolt and the Inhumans get Uncanny! Can the silent king stay quiet when Queen Medusa finds new love with the Human Torch? Or will the situation erupt in a battle of sound and fury and fire? Johnny Storm isn't the only new recruit to the Inhuman cause — the X-Men's Beast is on their side! And they'll need all the help they can get when they face the most dangerous villain throughout history: Kang the Conqueror! Kang's battleground covers thousands of years, and he'll attack the Inhumans in a horrifying fashion. What move will Kang make, millennia ago, that will wreak havoc in the present — and which Inhuman will work with him?